Empirical analysis of AI adoption for talent acquisition: a study on technological, organisational and demographic determinants / Parveen Kumari, Richa Sharma and Jyoti Chandwani - Kumari, Parveen; Sharma, Richa; Chandwani, Jyoti (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Integrating Artificial Intelligence (AI) in talent acquisition is changing recruitment processes, yet the factors influencing its adoption remain underexplored. The main factors affecting the usage of AI technologies in talent acquisition across various organizations are examined in this study. Utilizing the TOE model and Demographic characteristics, the research examined variables such as complexity, compatibility, competition, management support, relative advantages, and security & privacy concerns. Data was collected through a questionnaire and online survey from 240 employees working in IT companies based in Delhi-NCR. Findings revealed that compatibility, competition, relative advantages, and security issues significantly influenced AI adoption. Additionally, demographic variables such as income, professional experience, age, and education moderated these relationships. The results provide actionable insights that HR managers, AI developers, and organizational leaders can use to enhance the effective implementation of AI in recruitment. The study adds to the literature by offering a framework that bridges theoretical concepts with practical applications, guiding organizations in leveraging AI to optimize their hiring strategies.